2023
DOI: 10.1155/2023/2827938
|View full text |Cite
|
Sign up to set email alerts
|

To Investigate the Potential Mechanism of Huanglian Jiangtang Formula Lowering Blood Sugar in View of Network Pharmacology and Molecular Docking Technology

Abstract: Objective. In view of network pharmacology and molecular docking technology, to explore the targets as well as effect mechanism of the Huanglian Jiangtang formula (including Coptis chinensis, Anemarrhena asphodeloides, rhubarb wine, Cortex Moutan, Rehmannia glutinosa, and dried ginger) in the type II diabetes therapy. Methods. TCMSP and Batman database (DB) were used to retrieve the chemical components and action targets of drugs; GeneCards, OMIM, TTD, DrugBank, and other databases were applied to screen the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Yang-Fu and so on reported that Lichong Shengsui Decoction regulated cell cycle arrest and decreased the number of stem cells in ovarian cancer in 2019 17 . However, these literature reports were limited studies because they were performed in unilateral ways and affected by restrained factors, and could not reveal the full landscape of its mechanisms by multigenes, multitargets, multiple pathways, and integrated regulation 20 . The technology of network pharmacology integrated with molecular dynamics recently widely employed in the analysis of traditional Chinese medicine overcome the above-mentioned di culties.…”
Section: Introductionmentioning
confidence: 99%
“…Yang-Fu and so on reported that Lichong Shengsui Decoction regulated cell cycle arrest and decreased the number of stem cells in ovarian cancer in 2019 17 . However, these literature reports were limited studies because they were performed in unilateral ways and affected by restrained factors, and could not reveal the full landscape of its mechanisms by multigenes, multitargets, multiple pathways, and integrated regulation 20 . The technology of network pharmacology integrated with molecular dynamics recently widely employed in the analysis of traditional Chinese medicine overcome the above-mentioned di culties.…”
Section: Introductionmentioning
confidence: 99%